Microfungi Associated with Leaf Spot of Cocoa in Pahang, Malaysia - Mohd Zainudin, Nur Ain Izzati; Rosli , Muhamad Najmi Haikal; Wan Ahmad Kamal, Wan Halimah As-Sa’adiah; Azahar, Nuráin; Nordin, Nor Aisyah; Salleh, Suhaida; Yusof, Mohd Termizi; Ikhsan, Zahlul (Jurusan Budidaya Perkebunan, 2025)
Crop diseases caused by fungal infections have significantly impacted cocoa production, leading to substantial economic losses due to ineffective disease management strategies. Leaf spot disease, in particular, threatens cocoa yield and quality, necessitating accurate identification of its causal agents for effective control measures. This study aimed to isolate, identify, and assess the pathogenicity of fungal species associated with cocoa leaf spot disease. A total of 45 microfungal isolates were obtained from infected cocoa leaves and identified to the genus level, including Aspergillus, Clonostachys, Colletotrichum, Curvularia, Diaporthe, Fusarium, Lasiodiplodia, and Nigrospora species. Pathogenicity tests revealed that 12 isolates induced lesions on cocoa leaves, confirming their pathogenic potential. Molecular identification using internal transcribed spacer (ITS) sequence analysis verified the species identity of the pathogenic isolates, with Lasiodiplodia theobromae (B3418) exhibiting the highest virulence, producing lesions of 3.17 ± 0.76 mm. These findings highlight the diverse pathogenic fungi associated with cocoa leaf spot disease. This study provides valuable insights into fungal pathogenicity and can contribute to the development of effective disease management strategies, which can reduce fungal infections and improving cocoa productivity.